A variant octamer motif in a Xenopus H2B histone gene promoter is not required for transcription in frog oocytes. - Hinkley, C (1991)
Xenopus oocytes, arrested in G2 before the first meiotic division, accumulate histone mRNA and protein in the absence of chromosomal DNA replication and therefore represent an attractive biological system in which to examine histone gene expression uncoupled from the cell cycle. Previous studies have shown that sequences necessary for maximal levels of transcription in oocytes are present within 200 bp at the 5' end of the transcription initiation site for genes encoding each of the five major Xenopus histone classes. We have defined by site-directed mutagenesis individual regulatory sequences and characterized DNA-binding proteins required for histone H2B gene transcription in injected oocytes. The Xenopus H2B gene has a relatively simple promoter containing several transcriptional regulatory elements, including TFIID, CBP, and ATF/CREB binding sites, required for maximal transcription. A sequence (CTTTACAT) in the H2B promoter resembling the conserved octamer motif (ATTTGCAT), the target for cell-cycle regulation of a human H2B gene, is not required for transcription in oocytes. Nonetheless, substitution of a consensus octamer motif for the variant octamer element activates H2B transcription. Oocyte factors, presumably including the ubiquitous Oct-1 factor, specifically bind to the consensus octamer motif but not to the variant sequence. Our results demonstrate that a transcriptional regulatory element involved in lymphoid-specific expression of immunoglobulin genes and in S-phase-specific activation of mammalian H2B histone genes can activate transcription in nondividing amphibian oocytes.